Soils developed on the Si-poor, alkali-rich pyroclastic rocks of the Colli Albani volcanic district (Central Italy): The effect of leucite, clinopyroxene and phlogopite on the base cations mobility. (October 2022) - Gaeta, M.; Aldega, L.; Astolfi, M.L.; Bonechi, B.; Marra, F.; Pacheco, P.; Perinelli, C.; Tiberi, F.
Abstract: The Colli Albani volcanic district emplaced huge pyroclastic-flow deposits up to 20 m thick in the southeastern suburbs of the City of Rome. The soil quality onto the gentle slopes of the Colli Albani has certainly contribute to the growth of Ancient Rome, a city with one million inhabitants as early as 2000 years ago. Interestingly, the Colli Albani soils developed on K-foiditic pyroclastic rocks with peculiar low silica, high alkali and high CaO composition. In the past, the productivity of the Colli Albani soils was maximized without the understanding of the unique physical, chemical, and mineralogical properties of these soils; now an in-depth knowledge of the Colli Albani soils is necessary to respond to the current and increasingly demand of sustainable soil use. Textural, mineralogical and chemical data indicate that the evolutionary stages of soil development are bedrock →leucite (Lct)-bearing soils→quartz (Qz)-bearing soils. The bedrock is made up mainly of leucite, clinopyroxene, phlogopite, zeolites and K-foiditic glass that is turned in an amorphous phase characterized by the Al-rich, cations base-poor and hydrated composition (i.e. halloysite-like chemistry). This reaction occurs in the syndepositional conditions (i.e. temperature up to ∼600 °C) and causes the absence of glass and the abundant crystallization of halloysite in the Colli Albani soils. The Lct-bearing soils are organic matter-poor, weakly weathered volcanic matter, comparable to the vitric andosols, showing incipient halloysite crystallization. As the degree of weathering increases, i) grain size decrease, ii) pH remain neutral, iii) highly soluble leucite, analcime and other zeolites, are rapidly dissolved, iv) alkali, Ca and Mg are leached, v) silica, Al and Fe activities increase and vi) halloysite stability field enlarges. The resulting Qz-bearing soils are made up mainly of halloysite, quartz, oxy-phlogopite and calcic clinopyroxene showing a lower cation exchange capacity (CEC) compared to the Lct-bearing soils. However, in Qz-bearing soils the CEC it is rarely <20 cmol (+)kg −1 because KEx, MgEx and CaEx are released from the oxy-phlogopite and the strongly weathered clinopyroxenes characterized by the "gothic" texture. Highlights: Evidences of authigenic quartz in volcanic soils developed on silica-poor pyroclastic rocks. Incipient halloysite formation in volcanic soils from high-temperature, cations base depleted glasses. Gothic texture of clinopyroxenes in the Colli Albani soils.